Pemahaman Mata Ajar Nasionalisme Calon Pegawai Negeri Sipil - Agus Sediadi Tamtanus; Hubertus Oja (Universitas Musamus, Merauke, Papua, 2022)
Planting the spirit of nationalism as a conscious effort to realize the state civil apparatus that has a love for the state in providing its service to the community through service by upholding the values of Pancasila and piety to God Almighty. The implementation of nationalism is one of the efforts to minimize the influence of radicalism in the campus area. The purpose of this study was to evaluate participants' understanding of nationalism. To measure participants' understanding using pre-test and post-test methods. The results showed that academic examinations, nationalism teaching points were recorded on average between 86.47-89.90. This gives an indication that the understanding of nationalism can be well understood. The high sense of nationalism of participants is characterized by the presence of many from outside Merauke from various regions in Indonesia to serve as civil servants. The Internalization Stage of the Basic Values of the Civil Servant Profession, especially Nationalism is included in the satisfactory category; Stage of Formation of Attitudes and Behaviors Of Civil Servants, this stage of learning equips participants with the ability to improve disciplined behavior, physical and spiritual health as satisfactory public servants; The Actualization Stage, the learning stage of participants in actualizing the basic values of the Civil Servant Profession, regarding knowledge about the position and role of civil servants in the Unitary State of the Republic of Indonesia entered the category of satisfactory.